Advance Modelling and Simulation of Induction Motor Using Matlab: A Comprehensive Approach to Design and Performance Optimization - MOHAMMAD DANIEL FAIZ BIN MOHD NORRISHAM,; ZAMRI BIN NORANAI, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project presents the modelling, simulation, and performance evaluation of a three-phase induction motor using MATLAB. The main objective is to design an accurate analytical model that calculates essential motor parameters, including flux density, magnetizing reactance, stator and rotor resistance, and leakage reactance, which are crucial for determining the motor’s overall efficiency and torque characteristics. To support this process, a Graphical User Interface (GUI) is developed using MATLAB to simplify the simulation workflow. The GUI allows users to input basic motor specifications and view real-time results such as torque-speed curves, efficiency metrics, and electromagnetic behaviour without complex coding. The simulation output shows consistent results with theoretical expectations, indicating that the system performs effectively and provides reliable design feedback. Overall, the project demonstrates that combining MATLAB’s computational power with GUI capabilities creates a practical and interactive platform for understanding, designing, and optimizing the performance of induction motors in academic and industrial applications.